2017
DOI: 10.1002/cbic.201700154
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Galactosylated Bifurcated Ligands with Nanomolar Affinity for Lectin LecA from Pseudomonas aeruginosa

Abstract: Lectin A (LecA) from Pseudomonas aeruginosa is an established virulence factor. Glycoclusters that target LecA and are able to compete with human glycoconjugates present on epithelial cells are promising candidates to treat P. aeruginosa infection. A family of 32 glycodendrimers of generation 0 and 1 based on a bifurcated bis-galactoside motif have been designed to interact with LecA. The influences both of the central multivalent core and of the aglycon of these glycodendrimers on their affinity toward LecA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 58 publications
(100 reference statements)
0
23
0
Order By: Relevance
“…After studying the impact of the cluster density, they have been able to identify nanomolar inhibitors for the lectin LecA from Pseudomonas aeruginosa . 25 All of these studies clearly demonstrated that the spatial arrangement of multivalent structures on surfaces favors stronger interactions with lectins than with monovalent ligands. However, these experiments allowed discrimination of ligands with significant differences in valency, thus leading to predictable data in the majority of cases.…”
Section: Introductionmentioning
confidence: 93%
“…After studying the impact of the cluster density, they have been able to identify nanomolar inhibitors for the lectin LecA from Pseudomonas aeruginosa . 25 All of these studies clearly demonstrated that the spatial arrangement of multivalent structures on surfaces favors stronger interactions with lectins than with monovalent ligands. However, these experiments allowed discrimination of ligands with significant differences in valency, thus leading to predictable data in the majority of cases.…”
Section: Introductionmentioning
confidence: 93%
“…In the chelate binding mode, multivalent ligands occupy at least two binding sites of the multivalent receptor (the lectin) simultaneously.A fter the first interaction, subsequent binding events are favoredo ver dissociation of the ligand-receptor complex, due to the high ligand concentration in close proximity to additional receptor binding sites and to the lower entropic cost of subsequent binding events. Chelate interactions have been shown to improve the affinity of clustered sugars compared with their monovalent references by severalo rders of magnitude on several multimeric lectin targets, [7][8][9] such as wheat germ agglutinin (WGA), [10] Shiga-like toxins from Escherichiac oli, [11][12][13] LecA and LecB lectinsf rom Pseudomonas aeruginosa, [14][15][16][17][18][19][20][21] dendritic-cell-specific ICAM-3 grabbing non-integrin( DC-SIGN), [22][23][24][25] and PHL from Gram-negative Photorhabdus asymbiotica. [26] In comparison, multivalent fucosides of FleA have been little studied,w ith the exception of au nique, recent report of ap otent hexavalent aryl-fucose mimetic.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Another approach to enhancei nhibitor interaction to LecA is through multivalent binding. Because LecA is at etrameric lectin andt he two closest binding sites are separated by about 26 , [17] various artificial scaffolds including dendrimers, [11,[18][19][20][21][22][23][24] clusters, [12][13][14][25][26][27][28][29][30][31][32] and linear rigid spacers [33][34][35][36] have been exploited to present galactoside ligands to theb inding sites to enhancei nhibition activity. [37] In other cases, the artificial scaffoldsa re furtherf unctionalized to generate extra interactions with LecA for stronger binding.…”
Section: Introductionmentioning
confidence: 99%